Pengaruh Pengetahuan Tentang Peraturan Perpajakan Dan Tingkat Kepercayaan Sistem Pemerintahan Hukum Terhadap Kemauan Membayar Pajak - Sari, Fangela Myas; Priatiningsih, Dian (Akuisisi : Jurnal Akuntansi, 2024)
This study aims to analyze the factors that affect the willingness to pay taxes on taxpayers of individuals who perform free work in the office of KPP Pratama Batang. The variables in this study are taxpayer willingness as dependent variable, knowledge of taxation regulation level of trust to government system and law as independent variable. The population in this study were free workers registered in KPP pratama stem. The sample used in this research is as many as 30 respondents are free workers registered in KPP pratama stem. Meanwhile, to answer the hypothesis in this research is done classical assumption test and multiple linear regression. The result of the research shows that knowledge about taxation regulation, have no significant effect but Level of Trust in Government and Legal Systems have significant effect on taxpayer willingness.